Produksi dan Aplikasi Lakase pada Pembuatan Pulp: Sebuah Tinjauan - Hendro Risdianto (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2016)
Laccase is one of the promising enzymes in the production process of pulpmaking especially for the delignification process. This enzyme is belonging to the oxidative enzymes that can be produce mainly by white rot fungi. A large scale production of this enzyme is necessary for its availability. Production system for this enzyme has been studied both by submerged fermentation and solid state fermentation. For the applications, a pulping and a bleaching process can utilize this enzyme that can reduce the chemical consumption and pollution loading to the environment without reduce the properties of pulp produced.